Analisis Proses Pengelolaan Obat Dengan Pendekatan Lean Hospital Di RSUD X Kabupaten Jombang - Muhamad Aulia Putra Tawakal; Jason Merari Peranginangin; Gunawan Pamudji Widodo (Fakultas Farmasi Universitas Setia Budi, 2022)
The lean approach can make hospitals become more organized so they can improve the quality of services to patients by reducing waste, including the occurrence of errors, movements, transportation and poor service flow that leads to long service waits which certainly is not expected by patient. The purpose of this study was to identify the waste and the root causes of waste that occurred in the Pharmacy Installation at RSUD X Jombang. This research method is a qualitative descriptive study. The stages of the research are the observation of the drug management process flow which is made in the form of value stream mapping, focus group dicussion, and fishbone diagrams to determine the root cause of the problem. The results showed that the waste in the procurement process of 96.07% included in the category of necessary but non-value added, the acceptance process amounted to 62,59% of activities included in the category of necessary but non-value added, in the storage process there was a waste of 53, 39% included in the category of non value added, and in the process of using waste by 36.22% included in the category of non value added. The root cause of the problem of procurement is the length of time it takes to request the approval of PPK and PPTK, at the reception there is no specific place for receipt of goods, in storing all records and reporting is still manual and in use there is only one prescription receipt and delivery of drugs. In the future state mapping it is known to save time by 45.60% on procurement, 58% on revenue, 53.39% on storage, and 69% on usage.